A disease called stigma: the experience of stigma among African men with TB diagnosis in London. (April 2017) - Chinouya, M.J.; Adeyanju, O.
Abstract: Objectives: Tuberculosis (TB) is a highly stigmatised disease. This paper sought to explore the experiences and meanings of stigma among African men with a previous TB diagnosis. Study design: Qualitative approach with ten men recruited from a community based organisation offering health support to the men. Methods: In-depth semi-structured interviews. Results: Men were unable to recognise TB symptoms and subsequently made late clinical presentation when they were also diagnosed with HIV. A few were diagnosed when in immigration detention centres. The experience of late diagnosis informed their understanding of the word stigma. The link between HIV and TB compounded experiences of stigma which led to depression and compromised HIV confidentiality. Conclusion: TB late diagnosis among the men has implications for population health. Multidisciplinary teams supporting ongoing TB education programmes should include African men's organisations, due to the close supportive links such organisations have with African men. Highlights: Little is known about the experiences of TB-related stigma amongst African men in London. Late diagnosis influenced men's understanding and experiences of 'stigma'. Men were diagnosed in institutions namely hospitals and immigration detention centres. 'Public' awareness about the link between TB and HIV compromised men's HIV-confidentiality. Men were less able to recognise TB symptoms and treatment pathways.